Zimra performance appraisal system - Kasiyandima, Clayton (Midlands State University, 2015)
The manual staff appraisal system at ZIMRA is slow and tiresome due to the length of time it takes to generate and fill in individual employees’ evaluation forms resulting in low throughput of employees. The process is also not cost effective to the company as voluminous appraisals are posted to the head office for evaluation and back for feedback. The analysis phase saw the researcher using various data gathering methodologies which included interviews, questionnaires and focus groups among others. Therefore, from the analysis the researcher proposed development of a performance appraisal system that centrally locates all performance appraisal information within a formal framework. A detailed feasibility study was carried out and it resulted feasible to design the system and an in-house development solution was recommended. Various designing tools have been used which includes MYSQL and PHP servers. The system allows employees to fill appraisal forms online and submit them online. \Automated score cards computation, and feedbacks will provide the important features of the system. The system was successfully implemented and parallel changeover was the recommended changeover strategy due to its many advantages over other strategies. Maintenance was carried out using perfective maintenance strategy which allows for continual improvement of the system. It’s the view and aspirations of the researcher to have the system integrating the training modules which manages recommended training schedules in a bid to continuously cope with changing technological environment.